KOMPRESI DAN DEKOMPRESI FILE DENGAN MENGGUNAKAN ALGORITMA HALF-BYTE - Resdi Hadi Prayoga (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Yudharta Pasuruan)
File compression problem is one important aspect of information technologydevelopment. Compression is used for various purposes including: data backup, datatransfer, and one part of data security. The size of files sometimes become obstacles in thedelivery of this data. Large file transfer will take longer than the file sizesmaller.Sometimes there is a risk can not be accommodated on a storage medium and nottersampaikannya, so that will minimize the vacant capacity in the memory storage medium. Therefore, humans are always trying to find an alternative way to handlethis problem, one with compression techniques or reduce the file size.  The expected benefits of this research is the acquisition capacity or a smaller filesize and compare the ratio of original file size with file compression using the Half-Bytealgorithm.  Research carried out by using the Half-Byte algorithm that utilizes four bits to theleft which is often similar in sequence, especially in a text file. When the characters thesame first four bits received in a row seven times or more, these algorithms compress datawith a marker bit and then the first characters of the same row of four bits followed by apair last four bits of the next row and covered with bits of cover.